Creativity in magazines and working with publishers - Manwaring, Tony (Henry Stewart Talks, 2009)
The environment, M&S lingerie case study, It's a scary place for brands, Implicit magazine values: trust, relevance, signposts and publishers knowledge, Case studies: British Army, Lucozade Sport, DfT driving and drugs
Archived at 2022/11/27